Sistem Pengendalian Intern Pemerintah, Komitmen, Budaya Organisasional dan Good Government Governance dengan Kinerja Pemerintah sebagai Variabel Intervening - Widyasanti, Yolanda Suci; Misra, Fauzan (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p06, 2023)
This study aims to examine the effect of the government's internal control system, organizational commitment and organizational culture on good government governance with local government performance as an intervening variable. The research was conducted at the Regional Apparatus Organization (OPD) of West Sumatra Province. The research population is all employees in the West Sumatra Province OPD. The sampling technique used was saturated sampling with a total of 208 respondents. The research data analysis method is Partial Least Square (PLS). The results showed that the government's internal control system on good government governance through government performance had a positive and significant effect, organizational commitment to good government governance through government performance had no effect, and organizational culture on good government governance through government performance had a positive and significant effect. Keywords: SPIP; Organizational Commitment; Organizational Culture; Good Government Governance; Local Government Performance